Case Report: Atypical prostate cancer presentation: rectal bleeding, pain, and psoriasiform dermatitis - Obeng, Frank; Adamu, Aishah Fadila; Gavor, Samuel Edudzi; Setsoafia, Blessings Yao; Antwi, Ebenezer Kwame; Affram, Nelson; Ali, Ayamba Mamudu (Frontiers in Oncology, 2025)
Prostate cancer is typically asymptomatic and usually diagnosed through concerted screening programs. However, in settings where there are no existing national prostate cancer screening programs, it may be picked up at the clinics in patients presenting with urinary symptoms, erectile dysfunction, and hematospermia/hematuria. Rare atypical presentations may also occur, delaying diagnosis and management. This case report discusses a 61-year-old male of Black-African descent, whose first presentation to the hospital for a condition ultimately diagnosed as metastatic prostate cancer, was due to lower gastrointestinal bleeding, rectal pain, and psoriasiform dermatitis. The patient’s clinical findings included a moderate-sized (grade 2) nodular prostate on digital rectal examination (DRE), a total serum prostate-specific antigen (PSA) level of >200 ng/mL, low back bone pain, and osteoblastic lesions on lumbosacral spine X-ray. Prostate core biopsy histopathologically confirmed adenocarcinoma with a Gleason score of 4 + 4 = 8. Histopathological examination of the synchronous skin lesions revealed psoriasiform dermatitis. The patient was managed with surgical androgen deprivation therapy (ADT), followed by oral bicalutamide, dermatologist consultation, and blood transfusions. He was also scheduled for further radiotherapy and chemotherapy (to complete the multimodality prostate cancer treatment). This case highlights the importance of considering prostate cancer with atypical presentations and underscores the need for a multidisciplinary approach in managing advanced cases.